Palladium versus Platinum: The Metal in the Catalytic Center of a Molecular Photocatalyst Determines the Mechanism of the Hydrogen Production with Visible Light1. Issue 17 (22nd January 2015) - Pfeffer, Michael G.; Schäfer, Bernhard; Smolentsev, Grigory; Uhlig, Jens; Nazarenko, Elena; Guthmuller, Julien; Kuhnt, Christian; Wächtler, Maria; Dietzek, Benjamin; Sundström, Villy; Rau, Sven
Abstract To develop highly efficient molecular photocatalysts for visible light‐driven hydrogen production, a thorough understanding of the photophysical and chemical processes in the photocatalyst is of vital importance. In this context, in situ X‐ray absorption spectroscopic (XAS) investigations show that the nature of the catalytically active metal center in a (N^N)MCl2 (M=Pd or Pt) coordination sphere has a significant impact on the mechanism of the hydrogen formation. Pd as the catalytic center showed a substantially altered chemical environment and a formation of metal colloids during catalysis, whereas no changes of the coordination sphere were observed for Pt as catalytic center. The high stability of the Pt center was confirmed by chloride addition and mercury poisoning experiments. Thus, for Pt a fundamentally different catalytic mechanism without the involvement of colloids is confirmed.